2019
DOI: 10.1093/comjnl/bxz043
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of 2D&3D Video Watching of EEG Signals by Increasing PLSR and SVM Classification Results

Abstract: Despite the development of two- and three-dimensional (2D&3D) technology, it has attracted the attention of researchers in recent years. This research is done to reveal the detailed effects of 2D in comparison with 3D technology on the human brain waves. The impact of 2D&3D video watching using electroencephalography (EEG) brain signals is studied. A group of eight healthy volunteers with the average age of 31 ± 3.06 years old participated in this three-stage test. EEG signal recording consisted of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In [12], the researchers claimed that the behavior of brain signals did not change during 2D/3D TV watching. With the opposite result of this study, brain dynamics have been shown to exhibit different behaviors in the brain lobes and EEG frequency bands [49], [48], [5], [10]. Analysis of brain signals by watching 2D and 3D videos individually was done extensively in our previous studies [5], [10].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In [12], the researchers claimed that the behavior of brain signals did not change during 2D/3D TV watching. With the opposite result of this study, brain dynamics have been shown to exhibit different behaviors in the brain lobes and EEG frequency bands [49], [48], [5], [10]. Analysis of brain signals by watching 2D and 3D videos individually was done extensively in our previous studies [5], [10].…”
Section: Discussionmentioning
confidence: 96%
“…The configuration pattern of the electrodes is shown in Fig 1. Individuals were asked to sit on a comfortable chair about 85 cm from the TV (LG 32 inch) stand. The features of this television are detailed in [5]. Each EEG recording lasted approximately 135 s. Each test was repeated 5 times.…”
Section: Eeg Recording and Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the reasons why binocular vision is so important is that it allows to perceive depth and relationships between objects. EEG analysis of 2D and 3D technology can generally be classified as eye fatigue detection [17], game analysis [18], [19], detection of power spectrum differences in brain waves [20], [8], and investigation of the effects of stereoscopic disparity on event-related potentials [21]. Few of these studies have focused on a brief look analysis of brain signals in 2D and 3D video watching instead of comprehensive analysis, and none of them has examined the 2D and 3D transitions of video watching modes.…”
Section: Introductionmentioning
confidence: 99%
“…Acquiring and analyzing EEG signals are challenging. Various algorithms have been developed to efficiently process the EEG data, such as frequency analysis [3], wavelet transform [4], filter banks [5], hidden Markov models [6], support vector machines [7], and artificial neural networks [8].…”
Section: Introductionmentioning
confidence: 99%